Effects of Pilot Injection Timing on The Engine Performance of A Diesel Dual Fuel Engine - Jose da Silva; Dori Yuvenda; Bambang Sudarmanta (IPTEK The Journal of Engineering, 2019)
The combustion process in dual fuel diesel engines occurs sequentially starting with premix burning. The premix burning starts with the ignition delay process. The presence of CNG causes the ignition delay process to become longer, thereby reducing engine performance and increasing emissions on dual fuel diesel engines. This study uses diesel engine type Diamond DI 800 with dual fuel indirect injection model system. The method used a variation of diesel pilot injection timing 110 CA, 130 CA, 150 CA, 170 and 190 CA BTDC. Testing is done with a constant engine speed of 1500 rpm and loading 500 to 3000 watts with 500-watt intervals. The results show that by advancing the diesel pilot injection timing where brake horsepower and the average effective pressure between single fuel and dual fuel is not too far as the current and voltage changes generated by the generator are not too small. While optimal thermal efficiency increased by 4.11%, while CO and HC emissions decreased respectively by 10.85%  and 8.28% at occurred at the pilot injection timing 170 CA BTDC but still under the single fuel engine.